Colonization, Infection, and the Accessory Genome of Klebsiella pneumoniae - Martin, Rebekah M.; Bachman, Michael A. (Frontiers in Cellular and Infection Microbiology, 2018)
Klebsiella pneumoniae is a Gram-negative pathogen that has a large accessory genome of plasmids and chromosomal gene loci. This accessory genome divides K. pneumoniae strains into opportunistic, hypervirulent, and multidrug-resistant groups and separates K. pneumoniae from two closely related species, Klebsiella variicola and Klebsiella quasipneumoniae. Some strains of K. pneumoniae act as opportunistic pathogens, infecting critically ill and immunocompromised patients. These K. pneumoniae are a common cause of health-care associated infections including pneumonia, urinary tract infections (UTIs), and bloodstream infections. K. variicola and K. quasipneumoniae are often clinically indistinguishable from opportunistic K. pneumoniae. Other strains of K. pneumoniae are hypervirulent, infecting healthy people in community settings and causing severe infections including pyogenic liver abscess, endophthalmitis, and meningitis. A third group of K. pneumoniae encode carbapenemases, making them highly antibiotic-resistant. These strains act as opportunists but are exceedingly difficult to treat. All of these groups of K. pneumoniae and related species can colonize the gastrointestinal tract, and the accessory genome may determine if a colonizing strain remains asymptomatic or progresses to cause disease. This review will explore the associations between colonization and infection with opportunistic, antibiotic-resistant, and hypervirulent K. pneumoniae strains and the role of the accessory genome in distinguishing these groups and related species. As K. pneumoniae infections become progressively more difficult to treat in the face of antibiotic resistance and hypervirulent strains, an increased understanding of the epidemiology and pathogenesis of these bacteria is vital.